Datasets related to in‐land water for limnology and remote sensing applications: distance‐to‐land, distance‐to‐water, water‐body identifier and lake‐centre co‐ordinates. (November 2015) - Carrea, Laura; Embury, Owen; Merchant, Christopher J.
Abstract : Datasets containing information to locate and identify water bodies have been generated from data locating static‐water‐bodies with resolution of about 300 m (1/360 ∘ ) recently released by the Land Cover Climate Change Initiative (LC CCI) of the European Space Agency. The LC CCI water‐bodies dataset has been obtained from multi‐temporal metrics based on time series of the backscattered intensity recorded by ASAR on Envisat between 2005 and 2010. The new derived datasets provide coherently: distance to land, distance to water, water‐body identifiers and lake‐centre locations. The water‐body identifier dataset locates the water bodies assigning the identifiers of the Global Lakes and Wetlands Database (GLWD), and lake centres are defined for in‐land waters for which GLWD IDs were determined. The new datasets therefore link recent lake/reservoir/wetlands extent to the GLWD, together with a set of coordinates which locates unambiguously the water bodies in the database. Information on distance‐to‐land for each water cell and the distance‐to‐water for each land cell has many potential applications in remote sensing, where the applicability of geophysical retrieval algorithms may be affected by the presence of water or land within a satellite field of view (image pixel). During the generation and validation of the datasets some limitations of the GLWD database and of the LC CCI water‐bodies mask have been found. Some examples of the inaccuracies/limitations are presented and discussed. Temporal change in water‐body extent is common. Future versions of the LC CCI dataset are planned to represent temporal variation, and this will permit these derived datasets to be updated.